Sorption and Retention Behaviours of Benzene and Some Five-Membered Heterocycles on a Porous Graphitized Carbon Column - POLYAKOVA, Y.L.; ROW, K.H. (Asian Journal of Chemistry, 2010)
The sorption on a porous graphitized carbon column was tested by using benzene and some five-membered heterocycles as a sorbates. The performance of five solutes with two types of eluents was examined. The influence of mobile phase modifier on the retention was discussed. The Langmuir isotherm was applied to describe the adsorption of substances on the surface of the graphitized adsorbent. The parameters of the adsorption isotherms were compared with different mobile phase compositions. The exponential curves of benzene, imidazole, indole and indoline are logarithmically increased in pure aqueous eluent, but 1,2,4-triazole had showed linear adsorption isotherm. The solubility, solvophobic effects and selective interactions between solute polarizable or polarized functional groups with graphite affect the sorption of substances.